2022
DOI: 10.1097/yct.0000000000000821
|View full text |Cite
|
Sign up to set email alerts
|

Tardive Seizures After Electroconvulsive Therapy

Abstract: ObjectivesSeizures that occur spontaneously after termination of an electroconvulsive therapy (ECT) seizure are termed tardive seizures. They are thought to be a rare complication of ECT, influenced by risk factors that affect seizure threshold. However, there has been limited review of tardive seizures with modified ECT. We aimed to review the literature to provide clinical guidance for the use of ECT after tardive seizures.MethodsPubMed, EMBASE, PsycInfo, and CINAHL databases were searched from inception to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…3 To the extent that cognitive adverse effects are a concern in a particular patient, Miller et al 4 found that high power in the electroencephalogram theta band predicts greater acute cognitive adverse effects from high-dose right unilateral ECT, thus creating an opportunity to monitor the ictal electroencephalogram and accordingly adjust the stimulus dose early in the treatment course. A rarer adverse effect of ECT is the occurrence of tardive seizure after the ECT session, and the impression of the rarity of this event is confirmed in this issue of the Journal by Warren et al 5 On a different note, although ECT is an acknowledged strategy to quiet suicidal ideation, [6][7][8][9] the corresponding literature on transcranial magnetic stimulation (TMS) and suicidal ideation has been sparse. Therefore, we welcome the randomized clinical trial by Hines et al 10 showing that intensive, thrice-daily TMS was superior to sham TMS in rapidly relieving acute suicidal ideation.…”
mentioning
confidence: 87%
“…3 To the extent that cognitive adverse effects are a concern in a particular patient, Miller et al 4 found that high power in the electroencephalogram theta band predicts greater acute cognitive adverse effects from high-dose right unilateral ECT, thus creating an opportunity to monitor the ictal electroencephalogram and accordingly adjust the stimulus dose early in the treatment course. A rarer adverse effect of ECT is the occurrence of tardive seizure after the ECT session, and the impression of the rarity of this event is confirmed in this issue of the Journal by Warren et al 5 On a different note, although ECT is an acknowledged strategy to quiet suicidal ideation, [6][7][8][9] the corresponding literature on transcranial magnetic stimulation (TMS) and suicidal ideation has been sparse. Therefore, we welcome the randomized clinical trial by Hines et al 10 showing that intensive, thrice-daily TMS was superior to sham TMS in rapidly relieving acute suicidal ideation.…”
mentioning
confidence: 87%
“…4 Our patients developed tardive seizures within 30 minutes after the end of ECT-induced seizure, and they occurred early in the treatment course, which is consistent with a previous review. 5 They both needed loading doses of IV antiepileptic medications and stabilization in the ICU, and both were maintained on antiepileptic medications after discharge from ICU.…”
Section: Tardive Seizure In Patients With Intellectual Disabilitiesmentioning
confidence: 99%
“…Procedure details have recently been published. 5 Of 343 sessions in 30 patients included from April 27, 2021, to July 4, 2022, 198 sessions (57.7%) were bitemporal; 134 (39.1%), right unilateral; and 11 (3.2%), bifrontal stimulation. Therapeutic atropine was given for bradycardia or asystole in 17 sessions (5.0%), and prophylactic glycopyrrolate was given in 73 sessions (21.3%) (Table 1).…”
mentioning
confidence: 99%
“…Electroconvulsive therapy (ECT) is an effective neurostimulation therapy for major depressive disorders [1, 2]. Seizures during ECT (early prolonged seizures) and post ECT (tardive seizures) have been described [1].…”
Section: Figurementioning
confidence: 99%
“…Prolonged seizures after ECT are described in the literature and usually occur at the beginning of ECT [1]. Tardive seizures are less frequent [2]. Both are more frequently described in patients with treatment with other drugs that lower the seizure threshold (including lithium, bupropion and quetiapine) and with previous epileptiform abnormalities on EEG and brain lesions [4,5].…”
mentioning
confidence: 99%